NIGERIAN HERBAL MEDICINE PRODUCTS SOLD: A PILOT SURVEY (International Journal of Food and Nutritional Sciences, 2022)
Background: It is thought that the usage of herbal medicine is growing. The usage of unrefined medications is gradually being replaced with carefully prepared, developed, and recognised herbal medicinal products. The rising quantity of herbal medicine goods on store shelves in Nigeria is proof of this trend. Goals: In the Federal Capital Territory, Abuja, the survey's objectives were to inspect and record herbal medicine goods offered in pharmacies, retail stores, and mainly closed and open marketplaces. Methodology: An open-ended, semi-structured questionnaire was used as part of a cross-sectional study, and both descriptive and inferential statistics were performed. Results and Discussion: 95.7 percent of the medications stocked in open markets were crude. Just 26.1% of the vendors in the outdoor markets sold herbal medicine. In the FCT, oral administration accounts for more than 70% of the use of herbal medicines. Nigeria produces 68% of the world's herbal medicine products, with the most common indications being bitters and detoxification (26.4%), aphrodisiacs and fertility (16.7%), diabetes, and cardiovascular disease (10%). The percentage of products with a NAFDAC registration or listing was just 39.3%. There is a significant knowledge gap about the branding, packaging, and registration of herbal medications in open marketplaces.